Analysis And Improvement of Diesel Engine Performance Using Karanja Biodiesel - Prakash, Vodnala Veda; CM. Bagade; S. Suresh (International Journal of Psychosocial Rehabilitation, 2019)
One of the most effective strategies for reducing carbon dioxide emissions is switching to biodiesel, a renewable fuel that may be used in place of diesel. The experimental emphasis of this study is biodiesel refined from Pangomia Pinnata oil (Karanja oil). The physical and chemical properties of Karanja Biodiesel and its mixtures are investigated and compared to petroleum diesel. In addition, the performance characteristics of diesel engines fuelled with Karanja biodiesel were evaluated using blends of Karanja biodiesel (KB5, KB10, KB15, KB20, KB25) comprising 5%, 10%, 15%, 20%, and 25% of Karanja biodiesel, respectively. Under a constant load, the thermal efficiency, fuel consumption, and power of the brakes were evaluated at a range of engine speeds. We also used Response surface methods to zero in on the best set of operating settings for the engine under typical situations. The RSM model employed a CCD framework with three factors, five levels, and two blocks. Each goal was optimised using the response surface optimizer in the Minitab®16.2.1 statistical programme, and the optimal values for S (1900 rpm), B (13%), and T (33 N.m) were discovered to maximise engine performance while minimising fuel consumption.